The Effect of Chitosan-Based Edible Coating, Aloe Vera Extract with the Addition of Orange Pectin on the Shelf Life of Cut Pears: Pengaruh Edible Coating Berbasis Kitosan, Ekstrak Aloe Vera Dengan Penambahan Pektin Jeruk Terhadap Masa Simpan Buah Pir Potong - Muryeti, Muryeti; Sadida, Koulan (Department of Food Science and Biotechnology, Faculty of Agriculture Technology, Universitas Brawijaya, 2025)
Abstract Indonesia has an abundance of fruit, but they are prone to damage from mechanical, chemical, and microbiological factors. The use of edible coating made from chitosan, aloe vera extract, and citrus pectin can serve as an alternative packaging to protect fruit from contamination. This study aims to analyze the effect of use of aloe vera extract and chitosan in making edible coatings from orange pectin on the characteristics of cut pears. This study used a Completely Randomized Design (CRD) with a 2-factor factorial design to test the combination of edible coatings on sliced pears, with quality parameters such as weight loss, pH, and total soluble solids (TSS) over 6 days of storage at room temperature, analyzed using Two-Way ANOVA. The research stages started with the preparation of chitosan solution, the manufacture of edible coating from aloe vera, chitosan, pectin and application edible coating on pears. Quality tests were then carried out, including weight loss, pH, vitamin C content, total dissolved solids and organoleptics.The results showed that edible coatings significantly reduced weight loss, maintained total soluble solid, pH, vitamin C content, and organoleptic quality, extending the shelf life of sliced pears compared to untreated pears (control). The percentage value of weight loss was obtained at 0.0389%, while pH 3.5, TPT 7.0°Brix, vitamin C content 24.75 mg/10g, color preference reached 3.3, aroma preference reached 1.9 and texture preference reached 2.4.The optimal concentration was determined to be 2% aloe vera and 2% chitosan (V1K2). Abstrak Indonesia memiliki hasil buah yang melimpah, namun rentan rusak oleh faktor mekanik, kimia, dan mikrobiologi. Penggunaan edible coating berbahan kitosan, ekstrak aloe vera, dan pektin jeruk dapat menjadi alternatif kemasan untuk melindungi buah dari kontaminasi. Penelitian ini bertujuan untuk menganalisis pengaruh penggunaan ekstrak aloe vera dan kitosan dalam pembuatan edible coating dari pektin jeruk terhadap karakteristik buah pir potong. Penelitian ini menggunakan Rancangan Acak Lengkap (RAL) 2 faktorial yaitu konsentrasi aloe vera dan kitosan untuk menguji kombinasi edible coating pada buah pir potong dengan parameter mutu seperti susut bobot, pH, dan total padatan terlarut (TPT) selama 6 hari penyimpanan pada suhu ruang, serta dianalisis menggunakan Two Way ANOVA. Tahapan penelitian diawali dengan pembuatan larutan kitosan, pembuatan edible coating dari aloe vera, kitosan, pektin serta pengaplikasian edible coating pada buah pir. Setelah itu dilakukan pengujian mutu antara lain susut bobot, pH,kadar vitamin C, total padatan terlarut (TPT) dan organoleptik. Hasilnya menunjukkan bahwa edible coating dari ekstrak aloe vera, kitosan dan pektin berpengaruh dalam mengurangi susut bobot, mempertahankan TPT, pH, kadar vitamin C, dan kualitas organoleptik, memperpanjang masa simpan buah dibandingkan dengan buah pir tanpa perlakuan (kontrol). Nilai persentase dari susut bobot mencapai 0,0389%, pH 3,5, TPT 7.0°Brix, kadar vitamin C 24,75 mg/10g, kesukaan warna hingga skor 3,3, kesukaan aroma sampai skor 1,9 dan kesukaan tekstur mencapai skor 2,4. Konsentrasi optimal diperoleh pada konsentrasi 2% aloe vera dan 2% kitosan (V1K2).